Peran UN World Food Programme dalam Penanganan Krisis Pangan dan Kelaparan: Studi Kasus "Silent Hunger" di Niger - Ndaru, Herjuno; Defrina, Intan, Departemen Ilmu Hubungan Internasional, Universitas Indonesia (Global: Jurnal Politik Internasional, 2005)
The number of famine and hunger in Africa has increased sharply since 1990s. The problem is not only brought about by the lack of food, but also poverty as the embedded cause. Global partnership and cooperation are needed, instead of national government efforts in eradicating hunger. This article has some explanations. Firstly, it tries to pursue issue of global hunger as a humanitarian threat to the African; second it describes involvement of UN World Food Programme (WFP) in handling this crisis; and the last discussing the role of that organization, due to the function of WFP as a food aid agency. Arguments are built to criticize the role of WFP, too. The explanations refer to the case of food crisis in Niger August 2004 - July 2005.